Cephalometric evaluation of the relationship between cervical vertebral morphology and anomalies and the cranial base angle in different facial types and skeletal classes = Evaluación cefalométrica de la relación entre la morfología vertebral cervical y las anomalías y el ángulo de la base del cráneo en diferentes tipos faciales y clases esqueléticas - Ostovarrad, Farzaneh
This study examines the morphology and common anomalies of the cervical vertebrae in different skeletal classes and facial types. This cross-sectional study was conducted on 137 lateral cephalometric images of patients aged 18-55 years. The images were evaluated for fusion and posterior arch deficiency as the two most common anomalies along with cervical vertebral morphology (dense angle, the height of the posterior arch of the atlas, the external anterior posterior diameter of the atlas, and the cranial base angle). Data were categorized into three skeletal classes based on the Wits analysis and the ANB angle and also three facial types based on the SN-MP angle. These calculations were performed in SPSS 22 at the significance levelof P<0.05. The height of the posterior arch of the atlas was directly and significantly related to age and increased with it. The mean external anterior posterior diameter of C1 was higher in men and in the hypodivergent group. As for the other factors, including cervical spine anomalies, no significant relationship was observed with age, sex, skeletal classes, facial types, and the cranial base angle. Moreover, the mean morphology of the cervical spine was not significantly associated with skeletal classes. Based on the results, the height of the posterior arch of the atlas was associated with age and increased along with it. Moreover, the mean external anterior posterior diameter of the atlas was greater in men and in hypodivergent individuals.